Notes on ancient topography of Moesia Superior based on Roman itineraries (several examples from the Province of Kosovo and Metohija) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The paper considers the data about the problems of locating road stations and road communications in the province of Kosovo and Metohija. Researchers’ opinions about their locations differ. The basis of successful research of ancient road communications and settlements in the province of Moesia Superior is provided by written source materials and material remains. What is especially significant are the data from Tabula Peutingeriana, Ptolemy’s Geography and Anonymous Geographer from Ravenna, inscriptions, settlements and other material remnants. Archaeological findings point to the fact that Roman road network and settlements were developed in this area. Furthermore, the paper presents data concerning new observations about the remains of the road and settlements from this area. Due to data from written historical sources i.e. itineraries, and closer inspection of the terrain, we find out that in the area of Moesia Superior (The Province of Kosovo and Metohija) road stations on the main travel route Lissum-Naissus, namely Gabulеo, Theranda, Viciano, Vindenis, and Аd Fines were drawn. Data from ancient cartographic sources as well as the results of archaeological research of road communications in the Province of Kosovo and Metohija, in addition to significant facts that were presented, have not given a complete picture of the location of Roman travel routs and stations. However, on the basis of the abovementioned written sources which reveal the distance among road station, and due to material remains i.e. data from the area (saved road segments and milestones), marked routes of Roman road communications with road stations in the Province of Kosovo and Metohija were determined, which partly contributed to the ancient topography of this area being well known.